Loss of Individual and Social Identity: Consequences of Sexual Harassment of Iranian Nurses in the Workplace - Zeighami, Maryam; Mangolian Shahrbabaki, Parvin; Zakeri, Mohammad Ali; Dehghan, Mahlagha (Frontiers in Psychology, 2021)
Background: Sexual harassment in the workplace is a common event with negative consequences for victims. Working conditions become unstable because of sexual harassment, and workplace insecurity causes psychological distress and physical problems, as well as a reduction in the quality of care. Therefore, the current study sought to investigate the effects of sexual harassment in the workplace on Iranian nurses. Materials and Methods: This qualitative study used conventional content analysis with a descriptive-explorative approach to investigate the consequences of sexual harassment in Iranian nurses (n = 22). The purposeful sampling method was used. Semi-structured and in-depth interviews were used to collect data. Maximum diversity in terms of age, sex, work experience, level of education, marital status, and type of hospital and ward was observed in order to obtain rich information. The Guba and Lincoln criteria were used to improve the study’s trustworthiness and rigor, and the Graneheim and Lundman method was used to analyze the content. Results: Two hundred and twenty-seventh number codes, one main category, four subcategories, and eighteen primary categories were extracted from the data in this study. The main category of “loss of individual and social identity: the consequences of sexual harassment in nurses” is divided into four subcategories: “psychological trauma,” “detrimental effects of work,” “physical problems,” and “disintegration of warm family relationships.” Sexual harassment had a greater psychological impact on victims. Conclusion: Sexual harassment has a number of negative consequences for nurses’ personal and professional lives and can impose a significant burden on the healthcare system due to decreased productivity and loss of active labor. Therefore, it requires increased attention and focus.